К вопросу об актуальности системологического исследования процесса формирования компетенций менеджмента знаний - Соловьева, Екатерина Александровна; Панасовская, Юлия Валерьевна (НТУ "ХПИ", 2017)
Обоснована актуальность проведения исследований предметной области «Компетенции менеджмента знаний» с помощью системного подхода ноосферного этапа развития науки. Впервые выполнен анализ существующих подходов к определению понятий «компетенция», «компетентность», «компетенции менеджмента знаний» и предложены их рабочие определения с помощью системологического анализа. Исследованы и разработаны объектные модели требований к компетенциям менеджмента знаний и процессу их формирования. Предложенные модели могут быть использованы в качестве основ новой информационной технологии формирования компетенций менеджмента знаний.

The relevance of the weakly structured subject area "Knowledge Management Competences" research using the system approach of the noospheric stage of science development is substantiated. For the first time, the research of existing approaches to the definition of the concepts "competence", "competency", " knowledge management competences" made and proposed their system working definitions based on the systemological determinant analysis. The model of the requirements to the professional knowledge and skills of employees possessing knowledge management competences has been researched and developed. The model takes into account the knowledge and skills which are necessary to perform the basic functions and tasks of knowledge management (for example, "the application of the systemological classification analysis for knowledge representation"). The model of requirements to personal knowledge and skills of employees possessing knowledge management competences has been investigated and developed. Such a model formalizes and visualizes the employee basic personal characteristics, which are necessary for the successful performance of professional tasks (for example, "system thinking", "take the initiative," etc.). Research was conducted and the requirements model of the effective organizing of the formation knowledge management competences process (for example, the method of training, develop of a curriculum, etc.) was developed. The requirements to the knowledge management competences and to the process of their formation should be based on the mission, strategy and objectives of the organization, which are reasonably to determine by means of the systemological analysis. The received object models are presented in the article in the form of the Use Case UML diagrams fragments. The results of the research can serve as an information base for the knowledge management implementation in organizations; can be used as the basis for a new systemological information technology of the knowledge management competences formation for the effective and operational formation of such competencies.
On the question of systemological research importance of knowledge management competencies formation
Keywords: компетенции; компетентность; формирование компетенций; системология; системологический анализ; системологический классификационный анализ; информационная технология; конкурентоспособность организации; knowledge management; competences; knowledge management competences; requirements to competences; competences formation; systemology; systemological analysis; systemological classification analysis; competitiveness